2011
DOI: 10.3109/14992027.2011.637079
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Evaluation of Aural/Oral Performance of Children (PEACH) scale in the Malay language: Data for normal-hearing children

Abstract: The adapted version can be used to evaluate amplification for children in the Malay speaking environment. The normative curve relating age to scores for the Malay PEACH can be used as a reference against which functional aural/oral performance of hearing-impaired Malaysian children can be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
1
13
0
6
Order By: Relevance
“…The performance was assessed using adapted PEACH (Tamil). Tamil PEACH was administered to parents of Tamil children and follows the same procedure as used by Quar et al [34]. Test-retest reliability was obtained from six participants when the adapted scale was administered twice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance was assessed using adapted PEACH (Tamil). Tamil PEACH was administered to parents of Tamil children and follows the same procedure as used by Quar et al [34]. Test-retest reliability was obtained from six participants when the adapted scale was administered twice.…”
Section: Discussionmentioning
confidence: 99%
“…They found that African-American children obtained lower scores for receptive and expressive language when compared with European-American children. Thus parenting style (maternal sensitivity and negative intrusive maternal behavior), maternal education level, family stress, race, parent-child interaction, and cultural difference can affect language development of children [34]. Previous studies reported that Chinese parents, when compared to American and Canadian parents, are more restrictive, controlling, or authoritarian and less affectionate [4951].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, parental questionnaires were developed and are very useful tools for clinicians to obtain meaningful information regarding children's auditory performance in real life [4,7]. The ABEL questionnaire is a reliable subjective measure that may be suitable for this age group to express parents' perception of their child's everyday auditory abilities [9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, use of parental questionnaires is less timeconsuming for the clinician. Despite the known disadvantage of using a questionnaire, which is subjective, parental questionnaires are a well-established technique that was found to be suitable for monitoring progress [3,4].…”
Section: Introductionmentioning
confidence: 99%